An equation which is true for all real values of its variables is called an
identity. This is denoted by the symbol "º"
Show that the equation (a-b)2 = a2 - 2ab + b2 is an identity. Solution:
Substituting a = 2 and b =1 in the equation,
LHS = (2-1)2 = 12 = 1
RHS = 22 - 2.2.1 + 12
= 4 - 4 + 1
LHS = RHS. Hence equation is true for values 2 and 1.
Similarly it can be proved that the equation becomes a true statements for
any pair of real numbers
Direction: Show that the following equations are
in identities or not, taking any pair of real numbers and prove.